Optimized Triple-Slot Patch Antenna with Electromagnetic Band Gap Structures for Enhanced Performance - Chaduvula, Gowri; Kumari B, Leela (International Journal of Electrical and Computer Engineering Systems, 2025)
This paper presents an antenna integrated with an Electromagnetic Bandgap (EBG) structure to enhance its radiation performance compared to a conventional antenna. MEBG (Mushroom EBG) and EEBG (Edge via EBG) structures are analyzed, integrating MEBG with the triple-slot patch antenna, which demonstrates superior performance. Using the same conventional dimensions, the proposed antenna achieves a gain of 6.15 dB, a directivity of 7.51 dB, and a return loss of 37 dB at 5.2 GHz, providing a 1.92 dB gain improvement over the conventional design. This design is simulated using the HFSS software. The measurement results are validated with simulation results. The fabricated, compact antenna can be used for IoT applications at 5.2 GHz.